Astrocyte Networks as Therapeutic Targets in Glaucomatous Neurodegeneration - Boal, Andrew M. (Cells, 2021)
Astrocytes are intimately involved in the response to neurodegenerative stress and have become an attractive target for the development of neuroprotective therapies. However, studies often focus on astrocytes as single-cell units. Astrocytes are densely interconnected by gap junctions that are composed primarily of the protein connexin-43 (Cx43) and can function as a broader network of cells. Such networks contribute to a number of important processes, including metabolite distribution and extracellular ionic buffering, and are likely to play an important role in the progression of neurodegenerative disease. This review will focus on the pro-degenerative and pro-survival influence of astrocyte Cx43 in disease progression, with a focus on the roles of gap junctions and hemichannels in the spread of degenerative stress. Finally, we will highlight the specific evidence for targeting these networks in the treatment of glaucomatous neurodegeneration and other optic neuropathies.